Analysis of proposed geosites in the Betong District, Yala Province, Southern Thailand - Nazaruddin, Dony Adryansyah; Singtuen, Vimoltip; Baharim, Nor Bakhiah; Rahman, Muhd Nur Ismail Abdul (Geologos, 2023)
This study aims to analyse the geosite candidates of the Betong District (Yala Province) in Southern Thailand by means of several methods including inventory, characterisation, classification, assessment and SWOT analysis. Results of the present study are illustrated through seven proposed geosites that become resources for the development of the Betong District, namely Betong Hot Spring, Inthasorn Waterfall, Chaloem Phra Kiat Waterfall, Mount Silipat and Nakor Hot Spring, as well as Piyamit Tunnel and Aiyerweng Skywalk, two human-modified sites which can be used to observe geological and geomorphological features. The present study is expected to promote the conservation and development of these resources as geological heritage of the district.